Striking a balance: optimal tax policy with labor market duality - Foundation of Admirers and Mavens of Economics, Warsaw; Mbara, Gilbert; Kokoszczynski, Ryszard; Tyrowicz, Joanna (Warsaw, 2017)
"We develop a dynamic general equilibrium model in which firms may evade the employer contribution component of social security taxes by offering some workers “secondary contracts”. When calibrated, the model yields estimates of secondary labor market participation consistent with empirical evidence for the EU14 countries and the US. We investigate the optimal mix of the avoidable and unavoidable components of labor taxes and analyze the fiscal and macroeconomic effects of bringing the composition to the welfare optimum. We find that partial labor tax evasion makes tax revenues more elastic, but full tax compliance need not be a welfare enhancing policy mix."